2017
DOI: 10.1039/c7cs00555e
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer surface chemistry: conglomerateversusracemate formation on surfaces

Abstract: Research on surface chirality is motivated by the need to develop functional chiral surfaces for enantiospecific applications. While molecular chirality in 3D has been the subject of study for almost two centuries, many aspects of 2D chiral surface chemistry have yet to be addressed. In 3D, racemic mixtures of chiral molecules tend to aggregate into racemate (molecularly heterochiral) crystals much more frequently than conglomerate (molecularly homochiral) crystals. Whether chiral adsorbates on surfaces prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 341 publications
2
122
0
Order By: Relevance
“…They analyzed 1308 arbitrarily selected chiral organic compounds and found that ~90% of racemic mixtures crystallize as racemates and 5% to 10% of neutral, chiral organic molecules crystallize as conglomerates, whereas the probability of conglomerate crystallization of ionic and zwitterionic organic molecules is 2 to 3 times higher. These results found their way into reviews and textbooks of stereochemistry . A recent detailed review repeated the result of Jacques et al, mentioning that the formation of conglomerates increased at low crystallization temperatures …”
Section: Special Pointsmentioning
confidence: 53%
See 2 more Smart Citations
“…They analyzed 1308 arbitrarily selected chiral organic compounds and found that ~90% of racemic mixtures crystallize as racemates and 5% to 10% of neutral, chiral organic molecules crystallize as conglomerates, whereas the probability of conglomerate crystallization of ionic and zwitterionic organic molecules is 2 to 3 times higher. These results found their way into reviews and textbooks of stereochemistry . A recent detailed review repeated the result of Jacques et al, mentioning that the formation of conglomerates increased at low crystallization temperatures …”
Section: Special Pointsmentioning
confidence: 53%
“…These results found their way into reviews and textbooks of stereochemistry. [10][11][12][13] A recent detailed review repeated the result of Jacques et al, 14 mentioning that the formation of conglomerates increased at low crystallization temperatures. 15,16 In our analysis of 1179 amino acids, we checked whether they crystallized as conglomerates or racemates (column 10 en/rac in Tables S1-S19, Supporting Information).…”
Section: Conglomerate/racemate Crystallizationmentioning
confidence: 94%
See 1 more Smart Citation
“…Chirality is an important property and commonly used in biological functions and material sciences. Chiral ligands have attracted an extensively attention in chiral separation, asymmetric synthesis and catalysis, as well as supramolecular architectures due to their ability to generate an asymmetric environment . In principle, chiral ligands are employed to achieve enantio‐ or diastereoselective assembly, but a more complex and less explored situation arises when racemic ligands are used .…”
Section: Introductionmentioning
confidence: 99%
“…Chiral ligands have attracted an extensively attention in chiral separation, asymmetric synthesis and catalysis, as well as supramolecular architectures due to their ability to generate an asymmetric environment. [1][2][3][4][5][6][7][8] In principle, chiral ligands are employed to achieve enantioor diastereoselective assembly, but a more complex and less explored situation arises when racemic ligands are used. [9][10][11][12][13] In such systems, reactions with racemic ligands either result in homochiral complexes through a ligand self-recognition (also known as narcissistic self-sorting) process [14][15][16] or heterochiral complexes through a ligand self-discrimination (also called social self-sorting) process.…”
Section: Introductionmentioning
confidence: 99%